Effects of music and video on perceived exertion during high-intensity exercise - Enoch C. Chow; Jennifer L. Etnier (Elsevier, 2017)
Background: Dissociative attentional stimuli (e.g., music, video) are effective in decreasing ratings of perceived exertion (RPE) during low-to-moderate intensity exercise, but have inconsistent results during exercise at higher intensity. The purpose of this study was to assess attentional focus and RPE during high-intensity exercise as a function of being exposed to music, video, both (music and video), or a no-treatment control condition. Methods: During the first session, healthy men (n = 15) completed a maximal fitness test to determine the workload necessary for high-intensity exercise (operationalized as 125% ventilatory threshold) to be performed during subsequent sessions. On 4 subsequent days, they completed 20 min of high-intensity exercise in a no-treatment control condition or while listening to music, watching a video, or both. Attentional focus, RPE, heart rate, and distance covered were measured every 4 min during the exercise. Results: Music and video in combination resulted in significantly lower RPE across time (partial η2 = 0.36) and the size of the effect increased over time (partial η2 = 0.14). Additionally, music and video in combination resulted in a significantly more dissociative focus than the other conditions (partial η2 = 0.29). Conclusion: Music and video in combination may result in lower perceived exertion during high-intensity exercise when compared to music or video in isolation. Future research will be necessary to test if reductions in perceived exertion in response to dissociative attentional stimuli have implications for exercise adherence.